A clinical description of children with solid organ transplants who present with feeding disorder. (18th March 2019) - Lerret, Stacee M.; Erato, Gina; Goday, Praveen S.; Silverman, Alan H.
Abstract: Pediatric solid organ transplant recipients have long‐standing malnutrition concerns related to their pretransplant medical status. The targeted nutrition therapy utilized pre‐, peri‐, and post‐transplantation may have the adverse effect of impeding normally developing feeding skills, particularly in very young children. Little is known about the relationship between transplantation and feeding disorders of childhood. The purpose of this study was to describe severity of feeding disorder and parental stress in patients with transplant compared to children followed in a specialty feeding clinic and the general community. Sixty‐four children, comprised of 32 children with solid organ transplant ages 2 months to 12 years and 32 matched control patients diagnosed with a feeding disorder without history of solid organ transplant, were reviewed. All children were from the Feeding, Swallowing, and Nutrition Clinic at a single children's hospital. Findings indicate that patients who received a transplant and presented with a feeding problem had worse symptoms of feeding disorder than are typically found in the general community. These feeding problems disrupt mealtime behavior, caregiver and child relationship within a mealtime context, and may result in maladaptive feeding strategies used by families. When transplanted children present with feeding disorders, they are severe and have multiple effects on both the child and the feeding dynamic between the child and the child's caregivers. Further investigation may help us to better understand the relationship between transplantation and symptoms of feeding disorder.